S-Nitrosoglutathione is a component of wound- and salicylic acid-induced systemic responses in Arabidopsis thaliana - Espunya, M Carme (Journal of experimental botany, 2012)
S-Nitrosoglutathione (GSNO) is a bioactive, stable, and mobile reservoir of nitric oxide (NO), and an important player in defence responses to herbivory and pathogen attack in plants. It has been demonstrated previously that GSNO reductase (GSNOR) is the main enzyme responsible for the in vivo control of intracellular levels of GSNO. In this study, the role of S-nitrosothiols, in particular of GSNO, in systemic defence responses in Arabidopsis thaliana was investigated further. It was shown that GSNO levels increased rapidly and uniformly in injured Arabidopsis leaves, whereas in systemic leaves GSNO was first detected in vascular tissues and later spread over the parenchyma, suggesting that GSNO is involved in the transmission of the wound mobile signal through the vascular tissue. Moreover, GSNO accumulation was required to activate the jasmonic acid (JA)-dependent wound responses, whereas the alternative JA-independent wound-signalling pathway did not involve GSNO. Furthermore, extending previous work on the role of GSNOR in pathogenesis, it was shown that GSNO acts synergistically with salicylic acid in systemic acquired resistance activation. In conclusion, GSNOR appears to be a key regulator of systemic defence responses, in both wounding and pathogenesis